Lidocaine as an anti‐arrhythmic drug: Are there any indications left? - Sati Güler; Hilke Könemann; Julian Wolfes; Fatih Güner; Christian Ellermann; Benjamin Rath; Gerrit Frommeyer; Philipp Sebastian Lange; Julia Köbe; Florian Reinke; Lars Eckardt (Wiley, 2023)
Abstract Lidocaine is classified as a class Ib anti‐arrhythmic that blocks voltage‐ and pH‐dependent sodium channels. It exhibits well investigated anti‐arrhythmic effects and has been the anti‐arrhythmic of choice for the treatment of ventricular arrhythmias for several decades. Lidocaine binds primarily to inactivated sodium channels, decreases the action potential duration, and increases the refractory period. It increases the ventricular fibrillatory threshold and can interrupt life‐threatening tachycardias caused by re‐entrant mechanisms, especially in ischemic tissue. Its use was pushed into the background in the era of amiodarone and modern electric device therapy. Recently, lidocaine has come back into focus for the treatment of acute sustained ventricular tachyarrhythmias. In this brief overview, we review the clinical pharmacology including possible side effects, the historical course, possible indications, and current Guideline recommendations for the use of lidocaine.